The Possibility and Utility of Religious Science in Nasr’s Discourse of Traditionalism - Mohammadreza Khakigharamaleki (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی, 2017)
The study discuses Professor Seyed Hossein Nasr’s idea of traditionalism; a discourse of traditionalism that seeks to resurrect the divine science relied on divine tradition, perennial philosophy, and intuitive reason. In the negative dimension, acknowledging cognitive, moral, and environmental crises caused by modern sciences and their inefficiency as well, made him criticize these sciences and emphasize a return to the scientific tradition and philosophic heritage of the past. In the affirmative dimension, he emphasizes a return to the divine sciences and production of religious sciences as a savior of the situation. To him, the characteristics of divine sciences are: disassociation between metaphysical dimension and the physical dimension, longitudinal outlook towards the hierarchies of universe, symbolism, traditional scientific language, and avoiding utilitarian outlook. In fact, to return to tradition means to invite to be equipped with the past scientific tradition, to get free from western domination, and to be immune from the invasion of technology waves, social structures, and modern sciences. However such a support for scientific tradition is passive, because it loses to confront with modern sciences intelligently and from the standpoint of power. It is an invitation for solitary in order not to confront with west.